DEFINING AND CONTRIBUTING TO SOFTWARE DEVELOPMENT SUCCESS. (Communications of the ACM, 2006)
The article discusses the process-related components that affect software developers' perception of project success. Traditional definitions of software success focus on the completion of a project that meets customer requirements while remaining on time and on budget, but this definition may be too narrowly designed and skewed towards encouraging software developers to hire consultant firms. In order to arrive at a more insightful definition of project success, the article looks at software development from the perspective of developers.